Systematic Literature Review of Competitive Advantage and Marketing Capability of Small Medium Enterprises (SMEs) - Hanny Nurlatifah; Asep Saefuddin; Marimin Marimin; Heny Suwarsinah (Journal of Economics, Business, and Accountancy Ventura, 2021)
The discussion about the formation of competitive advantage in work organizations such as SMEs is still not widely discussed. The current literature still discusses marketing activities in general, not specifically for SMEs. This article aims to find out the factors that influence SMEs' competitive advantage and marketing capabilities. The literature review method systematically uses three stages. First planning for selecting source articles, second implementing and reporting stage. The PRISMA Literature Review Model selects articles and data visualization using VOS Viewer software. The findings of this article are the related potential relationships between marketing capabilities as forming competitive advantages for small and medium enterprises. Eleven topics are frequently discussed in a collection of journals, and the dominant words are sustainable marketing orientation, marketing, and Company Performance. The three groups can be grouped into personality development, business management, and abilities. Differences in the types of business groups and business sizes as differentiators of business performance results are not widely seen in article searches. These findings suggest further research to examine business groups' role and size in determining SMEs' competitive advantage and marketing capabilities.